CRUD-DOM: a model for bridging the gap between the object-oriented and the relational paradigms : an enhanced performance assessment based on a case study - Pereira, Óscar M. (2011)
the development of database applications comprises three different tiers: application tier, database tier and finally the middle tier also known as the data access layer. The development of each tier per-se entails many challenges. Very often the most difficult challenges to be addressed derive from non-functional requirements, as productivity, usability, performance, reliability, high-availability and transparency. This paper is focused on defining and presenting a model for the data access layer aimed to integrate object-oriented application tiers and relational database tiers. The model addresses situations on which users need to explicitly write down complex static CRUD expressions and simultaneously get advantages regarding some non-functional requirements. The model, known as CRUD Data Object Model (CRUD-DOM), tackles the following non-functional requirements: performance, usability and productivity. The main contributions of this paper are threefold: 1) to present an extended model of CRUD-DOM; 2) to carry out an extended performance assessment based on a case study; 3) to present a tool, called CRUD Manager (CRUD-M), which provides automatic code generation with complementary support for software test and maintenance. The main outcome from this paper is the evidences that the pair CRUD-DOM and CRUD-M effectively addresses productivity, performance and usability requirements in the aforementioned context.